2013
DOI: 10.1007/s10815-013-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

Rescue in vitro fertilization using a GnRH antagonist in hyper-responders from gonadotropin intrauterine insemination (IUI) cycles

Abstract: Objective To evaluate the outcomes in the conversion of high-response gonadotropin intrauterine insemination (IUI) cycles to "rescue" in vitro fertilization (IVF) using a Gonadotropin-Releasing Hormone (GnRH) antagonist, with regards to implantation rates, pregnancy rates, cost, and ovarian hyperstimulation syndrome (OHSS) as compared to matched, hyper-responder, IVF controls. Methods This prospective cohort study was conducted between January 2007 and December 2009 at our institution. In order to decrease hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Several studies of rescue IVF have all reported favourable outcomes when high response gonadotropin cycles were converted to IVF [27]. In a prospective cohort study published by our group, we showed that conversion of high-response gonadotropin-IUI cycles to 'rescue IVF' is a cost-effective strategy with relatively minimal morbidity, which provides better clinical outcomes than conventional IVF [26].…”
Section: Rescue Ivfmentioning
confidence: 67%
See 4 more Smart Citations
“…Several studies of rescue IVF have all reported favourable outcomes when high response gonadotropin cycles were converted to IVF [27]. In a prospective cohort study published by our group, we showed that conversion of high-response gonadotropin-IUI cycles to 'rescue IVF' is a cost-effective strategy with relatively minimal morbidity, which provides better clinical outcomes than conventional IVF [26].…”
Section: Rescue Ivfmentioning
confidence: 67%
“…Several studies of rescue IVF have all reported favourable outcomes when high response gonadotropin cycles were converted to IVF [27]. In a prospective cohort study published by our group, we showed that conversion of high-response gonadotropin-IUI cycles to ‘rescue IVF’ is a cost-effective strategy with relatively minimal morbidity, which provides better clinical outcomes than conventional IVF [26]. In addition, implantation and pregnancy rates were higher than those from hyper-responder IVF patients (≥ 14 collected oocytes) who have been started on mid-luteal long GnRH agonist protocols [26].…”
Section: Rescue Ivfmentioning
confidence: 67%
See 3 more Smart Citations